Current Needs and Difficulties in English Language Skill Faced by The Tourism Students - ., Ratnah (JOURNAL OF ADVANCES IN LINGUISTICS, 2019)
Recently, the development of tourism is increasing sharply and hotel industry has important role to support the tourism development in terms of providing the comfortable accommodation and excellent services and English language competencies should be possessed by the hotel employees in order to provide excellent services. However, some hotel employees still have low competence in English language skill. The purpose of this study is to find out the language skills that are mostly needed and categorized as the problems by the hotel employees in their work. This study employed quantitative study by using questionnaire and interview as the method of data collection. The sample of this study was taken by using purposive sampling by taking 30 tourism students who have just completed their six-month internship program in the industry. Based on the results of data analysis, it has been found that most language skills (listening, speaking, and writing) are categorized “High” used by the hotel employees, as their score between 3.41-4.20. While reading skills are categorized “Moderate” as its mean score between 2.61-3.40. And also All the language skills (listening, speaking, reading, and writing) are categorized “High” as problems faced by the hotel employees, as their score between 3.41-4.20.